2016
DOI: 10.37236/5312
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Complexes of Some Exponential Graphs

Abstract: In this article, we consider the bipartite graphs K 2 × K n . We first show that the connectedness of N (K Kn n+1 ) = 0. Further, we show that Hom(K 2 × K n , K m ) is homotopic to S m−2 , if 2 ≤ m < n.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…In [2], Babson and Kozlov showed that neighborhood complex of complete graph K m is homotopy equivalent to the (m − 2)-sphere S m−2 . In [25], Nilakantan and the author have studied the neighborhood complexes of the exponential graphs K Kn m . We have shown that N (K Kn m ) is homotopy equivalent to S m−2 for m < n. For all the above mentioned classes of graphs the bound given in (2) is sharp.…”
Section: Neighborhood Complexmentioning
confidence: 99%
“…In [2], Babson and Kozlov showed that neighborhood complex of complete graph K m is homotopy equivalent to the (m − 2)-sphere S m−2 . In [25], Nilakantan and the author have studied the neighborhood complexes of the exponential graphs K Kn m . We have shown that N (K Kn m ) is homotopy equivalent to S m−2 for m < n. For all the above mentioned classes of graphs the bound given in (2) is sharp.…”
Section: Neighborhood Complexmentioning
confidence: 99%
“…In [3], Björner and Longueville showed that the neighborhood complexes of a family of vertex critical subgraphs of Kneser graphs -the stable Kneser graphs, are spheres up to homotopy. In [10], Nilakantan and author studied the neighborhood complexes of the exponential graphs K Kn n+1 . In this article we compute the homotopy type of the neighborhood complexes of 4-regular circulant graphs.…”
Section: Introductionmentioning
confidence: 99%